Artificial Intelligence and Local Wisdom Integration in Maharah Qira'ah Learning: A Systematic Literature Review - Hibatullah, Nadhif; Imam Asrori; Ibnu Samsul Huda (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to synthesize the literature on the integration of Artificial Intelligence (AI), culture-based learning, and Maharah Qira’ah. Using a Systematic Literature Review (SLR) approach, 30 articles published between 2019 and 2026 were selected through predefined inclusion and exclusion criteria and analyzed using thematic synthesis. The findings indicate that AI supports personalized learning through adaptive instruction, automated feedback, and learning analytics. Culture-based learning enhances contextual relevance, learner engagement, and cultural identity, while digital innovations contribute to the development of reading literacy, reading comprehension, and critical reading skills. The review further reveals a strong conceptual relationship among these domains and proposes the concept of AI-Assisted Culture-Based Maharah Qira’ah Learning as a framework for adaptive, contextual, and culturally responsive Arabic reading instruction. This study contributes by bridging three research domains that have largely been examined separately and provides directions for future innovation in Arabic language education.